Effect of the film thickness on the impedance behavior of sol-gel Ba 0.6Sr0.4TiO3 thin films - Saif, Ala'eddin A.; Poopalan, Prabakaran, Assoc. Prof. (Elsevier B. V., 2011)
Link to publisher's homepage at http://www.elsevier.com/